Future Teachers’ Opinions on Preparation and Use of Interactive Materials in Teaching - Kassabolat, Aigul; Kadirsizova, Shynar; Kozybayeva, Makhabbat; Kalkeyeva, Kamaryash; Zhorokpayeva, Meiramgul; Aknur, Yerimova (International Journal of Emerging Technologies in Learning (iJET), 2020)
This study aims to determine the opinions of students in the primary education department about the preparation and use of materials with the teaching practice in Instructional Technologies and Material Design (TTMD) course. This study is a descriptive study based on qualitative data. The sample of the research consists of 49 students from the primary education department who took TTMD course at Almaty University in the 2018-2019 academic year. The data of the research were collected by structured interview form. According to the results, it has been revealed that primary school teacher candidates emphasized the importance on preparing and using materials based on their answers regarding the use and preparation of materials in teaching. When the opinions of primary school teacher candidates about the criteria that they value in preparing and using materials were examined, they emphasized the criteria such as suitability for the student level, fitness for the purpose, being clear and easy to understand. Moreover, the results showed that future primary school teachers have difficulty in finding materials and tools suitable for this purpose.